Use of Factorial Designs and the Response Surface Methodology to Optimize a Heat Staking Process - Faria Neto, Antonio [UNESP]; Costa, Antonio Fernando Branco [UNESP]; de Lima, Michel Floriano (Springer Nature, 2018)
The demand from the automotive industry for lighter and more resistant structures produced at lower costs has shifted the development focus of production processes toward hybrid components. A problem that arises from hybrid components is the necessity to join dissimilar materials, e.g., polymers and metals. A method to achieve this joining involves a process known as heat staking, in which a metal insert is heated and pushed against a thermoplastic surface. At the end of this process, the metal component may not be level with the thermoplastic surface; rather, it may be over flushed, and this discrepancy is known as the Insertion Height. This paper aims to apply the design of experiments and the response surface methodology to develop a model for the Insertion Height, considering the Heating Temperature and the Insertion Time as independent variables. The experiments revealed that the Insertion Height is most affected by the Heating Temperature. There are several combinations of the factors that can keep the Insertion Height within the specifications; therefore, it is possible to increase productivity by decreasing the Insertion Time and to save energy by reducing the Heating Temperature while considering the process constraints and specifications.
Keywords: Design of experiments; Factorial designs; Heat staking; Plastic welding; Response surface